Imagination in the creative process of kantele improvisation: Exploring the concepts of runosong culture in contemporary folk music - Väljaots, Eva (Taideyliopiston Sibelius-Akatemia, 2021)
This paper examines the connections between imagination and the creative process of improvising. In addition to that, pedagogical aspects of using imagination in music lessons were examined. The research question is: in what ways can imagination be part of the creative process of improvisation? In this research, the concept of ‘improvisation’ is applied stemming from the context of ancient kantele playing tradition. In the older layer of Finnish folk music, the runosong culture, the ancient zither-like string instrument kantele was central and the nature of music in runosong culture was improvisational. For conducting this research and analysing the data, principles of a qualitative approach were followed and for collecting the empirical data, semi-structured interviews were used. As the main findings, imagination is seen being inseparable from creativity and improvisation. To improvise, to ‘play one’s own power’, means to play one’s imagination and from that perspective, imagination is the core of improvising. Also, imagination is closely connected with the values that improvising has for the participants – the freedom of body and mind and non-judgemental thinking. Imagination is there in the improvisation through these values and at the same time carrying its essential quality of freedom. Moreover, using imagination in music lessons has long-term benefits for the students. It helps the students to find a personal relationship with the music, develop creativity and trust in themselves. Using imagination is a fruitful way of growing students’ well-being in education. I suggest that even nowadays the ancient kantele improvisation style which is the core of this research, is successfully applicable to other instruments and different musical situations. In addition, the impact of using imagination and improvising in music lessons could be seen in a wider social and cultural context. Using imagination in the teaching and learning processes and applying such values as freedom, equality and non-judgemental thinking could contribute into a better well-being in both, personal and societal level.
Keywords: musiikki; luovuus; improvisointi; kantele; mielikuvitus; runonlaulu; fi=kansanmusiikki|sv=folkmusik|en=Folk Music|